Effects of Industrial Experience, Education, Training, and Networking on Entrepreneurial Performance in Bandung City - Ahmad Zuhrofi; Dedy Wahyudi; Yusuf Iskandar; Kurniawan Kurniawan (Westscience Press, 2023)
This study aimed to investigate the effects of industrial experience, education, training, and networking on entrepreneurial performance in Bandung city. The study used a mixed-methods approach, including a survey of 150 entrepreneurs and case studies of five successful entrepreneurs in Bandung city. The results of the study provide evidence that all four independent variables are significant predictors of entrepreneurial performance. The strongest predictor is industrial experience, followed by education, entrepreneurship training, and networking. The findings of this study have important implications for policymakers, practitioners, and entrepreneurs who are seeking to improve entrepreneurial performance in Bandung city and other contexts.